2014
DOI: 10.1038/mt.2014.88
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vector Backbone and Pseudotype on Lentiviral Vector-mediated Gene Transfer: Studies in Infant ADA-Deficient Mice and Rhesus Monkeys

Abstract: Systemic delivery of a lentiviral vector carrying a therapeutic gene represents a new treatment for monogenic disease. Previously, we have shown that transfer of the adenosine deaminase (ADA) cDNA in vivo rescues the lethal phenotype and reconstitutes immune function in ADA-deficient mice. In order to translate this approach to ADA-deficient severe combined immune deficiency patients, neonatal ADA-deficient mice and newborn rhesus monkeys were treated with species-matched and mismatched vectors and pseudotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 54 publications
(82 reference statements)
1
13
0
Order By: Relevance
“…As observed in our prior studies, 9 , 16 Ada −/− mice in the Neonate group, treated with a single ADA LV administration, showed the highest vector copy number (VCN) in liver (0.337 ± 0.241 copies/cell) (Figure 1C). Similarly, marking was also highest in liver when mice were treated as Adults once (Adult 1×, 0.039 ± 0.0187 copies/cell) or twice within 3 days (Adult 2×, 0.026 ± 0.0114 copies/cell).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…As observed in our prior studies, 9 , 16 Ada −/− mice in the Neonate group, treated with a single ADA LV administration, showed the highest vector copy number (VCN) in liver (0.337 ± 0.241 copies/cell) (Figure 1C). Similarly, marking was also highest in liver when mice were treated as Adults once (Adult 1×, 0.039 ± 0.0187 copies/cell) or twice within 3 days (Adult 2×, 0.026 ± 0.0114 copies/cell).…”
Section: Resultssupporting
confidence: 83%
“…Ada −/− neonates treated with 5.0 × 10e9 TU/kg (1.0 × 10e7 TU/neonate) did not survive past day 30, while those treated with a 10-fold higher dose of 5.0 × 10e10 TU/kg (1.0 × 10e8 TU/neonate) survived with good immune reconstitution and resolution of the lethal pulmonary insufficiency 9 . In another related study, biodistribution analyses demonstrated differences in the amount of LVs detected in Ada −/− mice treated as newborns (at birth) compared to healthy infant rhesus monkeys treated at 1 month of age where no vector was detected in the rhesus thymus or brain 16 . However, it was not clear whether the differences observed were species-specific, developmental age-specific, or disease-specific.…”
Section: Resultsmentioning
confidence: 92%
“… 59 Self-inactivating vectors with a more random integration pattern, improved vector design, and lower vector doses are strategies that have shown success in reducing the risk of insertional mutagenesis while remaining efficacious in models of metabolic disease and immunodeficiencies. 51 , 60–63 Lentiviral transduced HSCs were effective in glycogen reduction in a Pompe disease mouse model, ameliorating the significant cardiac, respiratory, and skeletal muscle pathology. 51 , 52 One hypothesis for the effect is cross-correction of neighboring cells.…”
Section: Overview Of Therapies For Pompe Diseasementioning
confidence: 99%
“… 89 In order to reach the optimal vector copy number with a near to complete transduction of all cells in the graft, the transduction procedure itself needs to be optimized. 71 , 72 Parameters that can improve transduction efficiency are the viral coat proteins, 95 the use of growth factors and of polycations such as protamine, 96 and the ratio of vector to target cells. Consequently, the enrichment of hematopoietic stem cells by the use of cell surface markers can greatly reduce the amount of lentiviral vector required.…”
Section: Challenges In Gene Therapy For ß-Hemoglobinopathiesmentioning
confidence: 99%